Socioeconomic correlates of mental health in Moldova: A nationally representative door-to-door survey - J.M. van Baar; C. Ciofu; F. Thompson; A.I. Luik; O. Mereanu; J. Kramer; F. Schouten; V. Condrat; L. Voorham; J. Chihai; L. Shields-Zeeman (Journal of Affective Disorders Reports)
Background and Objectives: The mental health system in Moldova is transitioning toward a community-based model, which requires data on population mental health. This is the first mental health survey among a representative sample of the adult population. Methods: A stratified multistage sample (n = 1826) was collected using in-person door-to-door interviewing during July and August of 2022. The main outcome measures were depression symptoms (PHQ-2), anxiety symptoms (GAD-2), loneliness (UCLA-3), and mental well-being (WHO-5). Multivariable regression models were used to compare outcomes across age, gender, ethnicity, education, employment, and household income groups. Results: Prevalence was 19.8% for depression, 25.5% for anxiety, and 16.1% for loneliness. Average well-being was 69.6 out of 100. Women reported higher prevalence of depression and anxiety symptoms, more loneliness, and lower well-being than men. Older individuals reported higher prevalence of anxiety, more loneliness, and lower well-being than younger individuals. Individuals with low household income reported higher prevalence of depression and anxiety symptoms, more loneliness, and lower well-being than those with higher income, even when adjusting for education and employment. Conclusions: The study provides new data-supported insights into the target populations most at need of mental health support in Moldova (women, older adults, and those with low income) and provides baseline data for population mental health that can inform and guide future policy and research.